Women's Digital Expression: Advocacy for Women's Rights in Post-2015 Yemen through Social Media - Ulfianti Ulfi; Mohammad Izdiyan Muttaqin (Soshum: Jurnal Sosial dan Humaniora, 2026)
This article discusses women's advocacy in Yemen through social media following the outbreak of civil war in 2015 between the Houthis and the government of Abdu Rabbu Mansour Hadi. The novelty of this study is its integration of women's engagement in physical public spaces into digital ones and its emphasis on social media's role as an alternative public space for advocacy amidst the ongoing conflict, which limits conventional civic participation. The presence of Saudi Arabia as one of the major powers in the Middle East in the Yemen conflict has actually worsened the political instability in the country due to the intervention carried out by Saudi Arabia to prevent the Houthis from taking power in Yemen. To analyse, this study applies liberal feminist theory using a qualitative research design and analyses data narratively, drawing on primary and secondary sources. Through a case study of women in Yemen, the findings demonstrate how Yemeni women engage in digital advocacy by sharing personal experiences of gender-based violence, promoting legal awareness regarding women’s protection rights through written content, and fostering solidarity among women. Overall, the study shows that social media plays a crucial role in enabling women’s advocacy at a time when the state has been unable to ensure women’s safety and protection.